Mesenchymal stem cell secretome therapy on inflammation: A systematic review - Mutiara I. Sari; Nelva K. Jusuf; Delfitri Munir; Agung Putra; Imam B. Putra; Tatang Bisri; Farhat Farhat; Syafruddin Ilyas; Adi M. Muhar (GarVal Editorial Ltda., 2024)
Context: With recent biochemical studies, inflammation has been considered a therapeutic target. Mesenchymal stem cells are considered a therapeutic option because of the immunomodulatory effects of their bioactive factors, the secretome. Aims: To systematically review the potential of mesenchymal stem cell secretome therapy on inflammation through its effects on biomarker characteristics, organ damage, and survival rate. Methods: This study was conducted in accordance with the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) 2020 statement. A literature search was performed in PubMed, ScienceDirect, and ProQuest, and through citation searching for records published in the last ten years. The eligibility criteria of the identified study as follows: Population (P): Human, animal, or in vitro models with inflammatory disease; Intervention (I): Stem cell secretome administration; (C): Healthy human, animal, or in vitro models; and Outcome (O): Inflammatory biomarker statistics, organ injury, or survival rate. AXIS tool was used to assess the quality of the records. Results: 3,258 records were found. The duplicates and undesired articles were excluded with automation tools. 38 relevant records were further identified through citation searching. The screening and exclusion of records based on the inclusion and exclusion criteria left 24 eligible studies. The studies show that secretome improves the biomarker characteristics by reducing proinflammatory cytokines levels while increasing anti-inflammatory cytokines levels. Many studies show that secretome also improved organ injury and survival rate. Conclusions: Secretome alleviates inflammation with its immunomodulatory effects, which may be associated with improvements in organ injury and overall outcome.